2007
DOI: 10.1309/j64r-8020-2j71-2k80
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications in Patients With Hereditary Thrombophilia Identified Using the LCx Microparticle Enzyme Immunoassay: A Controlled Study of 5,000 Patients

Abstract: Factor V Leiden (FVL) and prothrombin (PT) G20210A mutations are associated with increased risk of deep venous thrombosis, pulmonary embolism, and obstetric complications. The development of inexpensive and reliable screening methods will assist in defining subpopulations of patients at risk who should undergo testing. We used a method, developed by Abbott Laboratories (Abbott Park, IL), to study 5,000 pregnant women and evaluated the association of obstetric complications with the presence of the FVL and PT G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Thus, as regards the FVL mutation among women with recurrent early pregnancy loss, thanks to appropriate controls and the large population enrolled, our study can be considered capable of detecting a clinically relevant difference between cases and controls. Our negative results are in accordance with an earlier study with a large recruitment of cases [20], some more recent studies [30,31] and the most advanced opinions, concerning first trimester recurrent loss, which do not consistently suggest an association with FVL mutation [27,29]. Our study should avoid the heterogeneity of cases and controls studied in meta‐analyses which have until now supported this growing point of view.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, as regards the FVL mutation among women with recurrent early pregnancy loss, thanks to appropriate controls and the large population enrolled, our study can be considered capable of detecting a clinically relevant difference between cases and controls. Our negative results are in accordance with an earlier study with a large recruitment of cases [20], some more recent studies [30,31] and the most advanced opinions, concerning first trimester recurrent loss, which do not consistently suggest an association with FVL mutation [27,29]. Our study should avoid the heterogeneity of cases and controls studied in meta‐analyses which have until now supported this growing point of view.…”
Section: Discussionsupporting
confidence: 88%
“…The overall cohort included 118 women who were heterozygous and four who were homozygous for the prothrombin gene G20210A mutation 26. Recently, Kocher and colleagues assessed a large cohort of unselected pregnant women for the factor V Leiden and prothrombin G20210A mutations 27. The factor V Leiden mutation was associated with an increased risk of stillbirth (OR 11.6, 95% CI 1.93–69.43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the role of Factor V Leiden and the prothrombin 20210 gene mutations are not conclusive, with some studies suggesting an important role in incidence of fetal loss and others being less clear [22, 23]. Another study which included over 5000 women found that there was indeed a strong association between Factor V Leiden and risk of stillbirth with an odds ratio of 10.9 [24]. In this study, there was not a similar association established for early fetal loss, and the prothrombin gene mutation was not associated with any increased risk.…”
Section: Outcomes Related To Thrombophilias In Pregnancymentioning
confidence: 99%